2020
DOI: 10.24815/jbe.v12i1.17277
|View full text |Cite
|
Sign up to set email alerts
|

Plant Diversity in Oil Palm Plantations in Tanjung Seumantoh, Karang Baru, Aceh Tamiang

Abstract: Penelitian ini bertujuan untuk mengetahui tingkat keanekaragaman tumbuhan di perkebunan kelapa sawit PT. Perkebunan Nusantara 1 PKS dan PIS desa Tanjung Seumantoh Kecamatan Karang Baru Kabupaten Aceh Tamiang. Penelitian menggunakan metode petak ganda, dimana luas petak untuk tumbuhan herba adalah 1m x 1m dan untuk semak adalah 5m x 5m, sedangkan untuk pohon dilihat kerapatan dan frekuensi secara keseluruhan. Data dianalisis menggunakan analisis nilai penting (NP), indeks keragaman (H'), dan indeks kemiripan (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Herbs are also adaptable to climate change, have allelopathy, and reproduce through seeds and stolons that spread easily. Old herb seeds are usually covered with fur and are small so that they are easily carried by wind and water or attached to the bodies of animals and humans (Widarta et al, 2020). This character makes herbaceous species generally pioneer plants.…”
Section: Vegetation Composition In Three Overburden Agesmentioning
confidence: 99%
“…Herbs are also adaptable to climate change, have allelopathy, and reproduce through seeds and stolons that spread easily. Old herb seeds are usually covered with fur and are small so that they are easily carried by wind and water or attached to the bodies of animals and humans (Widarta et al, 2020). This character makes herbaceous species generally pioneer plants.…”
Section: Vegetation Composition In Three Overburden Agesmentioning
confidence: 99%
“…This is because monocultures from oil palm plantations only focus on one type of oil palm. In addition, this type of plant species diversity is considered to be a competitor for oil palm in obtaining water and nutrients [7]. [8] revealed that undergrowth in oil palm plantations is often seen as weeds that are considered to competewith oil palm for nutrients, so plantation management overcomes with weeding and herbicides.…”
Section: Introductionmentioning
confidence: 99%